적분 슬라이딩 모드 관측기 및 퍼지 적분 슬라이딩 모드 제어 기반 전방향 이동로봇의 고장 허용 시각 서보 제어 - 장지영 (The Graduate School, Ajou University, 2024)
본 논문에서는 전방향 이동로봇(omnidirectional mobile robot, OMR)의 시각 서보 제어(visual servoing)에서 구동기 고장에 강인한 고장 허용 시각 서보 제어 기법을 제안한다. 기존 전방향 이동 로봇의 서보 제어 연구에서는 전방향 이동 로봇의 구동기 고장을 고려하지 않았다. 단일 카메라를 이용하는 전방향 이동로봇의 시각 서보 제어는 구동기 고장 발생시 제어 성능이 저하되고 이로 인해 목표물이 카메라 시야에서 이탈하여 시스템이 발산할 수 있다. 본 연구에서는 구동기 고장을 고려한 단일 카메라 기반 전방향 이동 로봇을 모델링하고, 구동기 고장을 추정하기 위한 적분 슬라이딩 모드 관측기(integral sliding mode observer, ISMO)를 설계한 후, 적분 슬라이딩 모드 관측기의 추정치를 이용하여 구동기 고장에 강인하고 과도응답 성능이 개선된 퍼지 적분 슬라이딩 모드 제어(fuzzy integral sliding mode control, FISMC) 기법을 설계한다. 기존 연구에서는 선형 모델을 통해 전방향 이동로봇의 구동기 마찰을 표현하므로 정지 마찰, Stribeck 효과와 같은 비선형적인 특성을 표현하지 못한다. 반면에 본 연구에서는 Stribeck 모델을 이용해 전방향 이동로봇의 동역학을 모델링하여 마찰을 보상한다. Stribeck 모델을 고려한 전방향 이동로봇의 동역학 파라미터를 식별하고 전방향 이동로봇의 동역학의 속도 출력과 실제 전방향 이동로봇의 속도 출력을 비교하여 식별률을 검증한다. 식별된 동역학 파라미터를 이용해 제안하는 적분 슬라이딩 모드 관측기 기반 퍼지 적분 슬라이딩 모드 제어(integral sliding mode observer based fuzzy integral sliding mode control, ISMO-FISMC) 기반 고장 허용 시각 서보 제어 기법에 대한 모의실험과 실험을 수행한다. 모의실험과 실험 결과를 통해 제안하는 기법의 타당성을 입증하고, 기존의 제어 기법과 비교하여 구동기 고장에 강인하며, 개선된 과도응답 성능을 확인한다.|In this paper, we propose fault tolerant visual servoing method in omnidirectional mobile robots with a single camera to ensure robustness against actuator faults. The actuator faults were not considered in the previous studies on visual servoing for omnidirectional mobile robots. Owing to actuator faults, the control performance of the visual servoing for an omnidirectional mobile robot could be deteriorated, and a target may deviate from the camera’s field of view. In most studies, the friction of omnidirectional mobile robots is represented as a linear model, ignoring the nonlinear characteristics of friction such as static friction and Stribeck effect. An ISMO-FISMC based fault tolerant visual servoing method for OMRs is proposed to compensate for the actuator faults and enhance transient response. We modeled omnidirectional mobile robot dynamics considering actuator faults and then designed the ISMO to estimate actuator faults. Using the estimates of the ISMO, an FISMC method is used to ensure robustness against the actuator faults and improve transient response performance. Therefore, to express nonlinear characteristics of the friction, omnidirectional mobile robot dynamics are modeled with Stribeck model and omnidirectional mobile robot dynamics parameters are identified. Simulations and experiments were performed for the proposed ISMO-FISMC based fault-tolerant visual servoing method using identified parameters. The simulation and experimental results prove the feasibility of the proposed method, confirming the robustness against actuator faults.
학위논문(석사)--전자공학과,2024. 2
Keywords: 고장 허용 제어; 시각 서보 제어; 적분 슬라이딩 모드 외란 관측기; 전방향 이동로봇; 퍼지 적분 슬라이딩 모드 제어기